Manajemen Desain Lingkungan Pada Program Kegiatan Pendidikan Paud Ramah Anak - Silma Humairo; Muhammad Imam Khaudli; Siti Aimah (Institut Agama Islam Negeri Madura, 2024)
Environmental design management is one of the management concepts that PAUD educational institutions believe is crucial and should be taught to students. environmental design for both indoor and outdoor spaces. This demonstrates that the early years of education are the golden era since brain development happens so quickly throughout this time. The purpose of this study is to provide an overview of PAUD Darussalam Blokagung Banyuwangi's environmental design activities and management process. This type of research uses qualitative methods with a descriptive approach. The data collection techniques use observation, interviews and documentation. Meanwhile, data analysis uses data reduction, data presentation and drawing conclusions. Research findings show that the early childhood education activity program at PAUD Darussalam Blokagung has an effective environmental design management system for all stages of planning, organizing, implementing and assessing. Meanwhile, the form of environmental design management consists of an indoor learning environment and an outdoor learning environment. The indoor environment consists of a study room, office and toilet. Meanwhile, in the outdoor environment, educators not only teach students through pictures and narratives, but also teach verbally to the views of the surrounding environment.